The Impact of Educational Leadership and Classroom Management on Students’ Learning Quality at MTs Mathla’ul Anwar Gunung Baru - Anthony Thamrin, Arie; Arjuni, Miming (GHAITSA : Islamic Education Journal, 2026)
This study aims to analyze the influence of educational leadership and classroom management on the quality of student learning at MTs Mathla’ul Anwar Gunung Baru. The research employed a quantitative approach with a causal associative survey design using multiple linear regression analysis, involving a sample of 212 students selected through proportional random sampling from a population of 372 students. Prior to analysis, the research instruments were tested for validity using Product Moment correlation and for reliability using Cronbach’s Alpha, with all variables meeting the acceptable threshold (α > 0.70). In addition, classical assumption tests, including normality, linearity, and heteroscedasticity, confirmed that the data met the requirements for regression analysis. The results indicate that educational leadership has a positive and significant effect on learning quality (β = 0.271; t = 4.443; sig. = 0.000). Similarly, classroom management also shows a positive and significant effect (β = 0.398; t = 6.862; sig. = 0.000), and is identified as the more dominant variable. Simultaneously, both variables significantly influence learning quality, with an F value of 152.6 (p = 0.000) and a coefficient of determination (R²) of 0.643, indicating that 64.3% of the variance in learning quality is explained by these two variables. The findings also suggest that leadership tends to exert an indirect andstructural influence, while classroom management operates more directly at the instructional level, resulting in stronger observable effects. The novelty of this study lies not merely in combining educational leadershipand classroom management, but in integrating both variables within a single regression model in the specific context of MTs (Islamic junior secondary schools) in Way Kanan, Lampung, which remains underrepresented in prior empirical research. This study provides context-specific empirical evidence that highlights the complementary relationship between leadership as a structural factor and classroom management as a pedagogical factor in determining learning quality. These findings imply that improving learning quality in madrasah settings requires an integrated approach that simultaneously strengthens leadership practices and classroom management competencies.